LONGITUDINAL DECLINE OF ANTI-S-RBD IGG ANTIBODY LEVELS AMONG LECTURERS AND EDUCATIONAL STAFF FIVE MONTHS AFTER CORONAVAC VACCINATION IN INDONESIA - Nurmila Sari; Yona Mimanda; Muniroh; Dinnisa Haura Zhafira Hidayat; Tri Nurjannah (Pena Cendekia Insani, 2026)
Humoral immunity induced by the CoronaVac vaccine may decline overtime. This study assessed changes in anti-spike receptor-binding domain (S-RBD) immunoglobulin G (IgG) antibody levels at 1 month and 5 months after completion of the two-dose CoronaVac regimen. A prospective observational cohort study was conducted among 54 participants, with 28 completing paired antibody measurements. Serum anti-S-RBD IgG concentrations were measured using a chemiluminescence microparticle immunoassay (CMIA), and differences between time points were analyzed using the Wilcoxon signed-rank test. A significant decline in antibody levels was observed, with the median concentration decreasing from 521.1 AU/mL (range: 71.2–2109.4) at 1 month to 57.8 AU/mL (range: 49.0–512.4) at 5 months, representing an approximately 89% reduction (p < 0.001). The Hodges Lehmann estimated median difference was -426.125 AU/mL (95% CI: -633.550 to -260.500). These findings indicate waning humoral immunity within five months after the second CoronaVac dose and support consideration of booster vaccination strategies.